Building a Technical Leadership Model. Issue 1 (13th September 2016) - Godfrey, Patrick
Abstract: INCOSE's Vision 2025 identifies the development of Systems Thinking and Technical Leadership as one of seven key areas of Systems Engineering 'Competency' required for delivery. Vision 2025 states: "Education and training of systems engineers and the infusion of systems thinking across a broad range of the engineering and management workforce will meet the demands for a growing number of systems engineers with the necessary technical and leadership competencies." "The roles and competencies of the systems engineer will broaden to address the increasing complexity and diversity of future systems." "The technical leadership role of the systems engineer on a project will be well established as critical to the success of a project." These requirements imply the need to rapidly expand the art and science of Systems Technical Leadership. In response to this need, INCOSE established the INCOSE Institute for Technical Leadership. This paper describes the Institute and the work that the first Cohort ("Cohort of 2017") has accomplished on developing a Technical Leadership Model for Systems Engineers. It is envisaged that this first Technical Leadership Model for Systems Engineers will be further developed and matured by the following cohorts of the INCOSE's Technical Leadership Institute.